Efeitos do nível educacional no êxodo rural no semiárido brasileiro - Asevedo, Moisés Dias Gomes de (2017)
The migratory processes of the countryside to the city have been inherent in the Brazilian semi-arid region. However, in addition to the need for a better quality of life, one of the main factors in the departure of the man from the countryside to the city is through a search for a greater Educational level, as reported in Theory of Human Capital. This migratory element brings the inferential hypothesis that the migratory process for the urban environment will make the rural population, in the semi-arid and non-semi-arid regions, aged and disproportionate to the genres. The analysis of the population indicators, of the productivity and of the index of schooling can help in the understanding of social phenomena related to the distribution of the population. The present work has the main objective of verifying how the search for personal qualification with regard to schooling has caused the rural exodus and, therefore, in the Brazilian semiarid, to analyze the behavior of the rural exodus in the Brazilian semiarid, to calculate the Index of Education For the Brazilian semi-arid region and to study the effect of educational policies on rural development in the region. The methodology of the present study will be based on the calculations of the demographic indicators and the application of the ordinary least squares regression model, described by Gujarati (2006) and Greene (2012), showing how much the level of education of the rural resident allied to the productivity will affect the rural exodus, aging, and gender ratios of Brazilian rural semiarid. In the study it was verified that the search for qualification and better living conditions has caused a decrease in the rural population and that it has presented an aged and masculinized population.